2021
DOI: 10.2147/prom.s272688
|View full text |Cite
|
Sign up to set email alerts
|

Women Diagnosed with Ovarian Cancer: Patient and Carer Experiences and Perspectives

Abstract: Purpose By directly engaging with women diagnosed with ovarian cancer, this study aimed to explore and identify their view of the health symptoms and outcomes that matter most to them as they traverse their disease pathway. Background Patient-reported outcome measures in ovarian cancer have tended to focus on physical symptoms rather than the more complex psychosocial aspects of living with the disease. Using a “ground-up approach”, this study sought to comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…The differences in outcome between these studies might be subjected to the patient population, especially benign versus malignant, or the different questionnaires used in the studies. It might be related to the coping style which might differ between different patient populations, since patients with malignant diseases might be more resilient and cope differently with health deficits following postoperative complications, leading to a relative underestimation of the effect of complications on HRQoL 26,27 . Time points of measuring HRQoL were not equal in all studies, however, most studies measured HRQoL within the first 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in outcome between these studies might be subjected to the patient population, especially benign versus malignant, or the different questionnaires used in the studies. It might be related to the coping style which might differ between different patient populations, since patients with malignant diseases might be more resilient and cope differently with health deficits following postoperative complications, leading to a relative underestimation of the effect of complications on HRQoL 26,27 . Time points of measuring HRQoL were not equal in all studies, however, most studies measured HRQoL within the first 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is a global problem that affects women of all ages but is most commonly diagnosed in the postmenopausal period [18,19]. Due to the lack of effective screening and the usually asymptomatic course of the disease in its early stages, more than 75% of affected women are diagnosed too late, resulting in less than half of the patients diagnosed with OC surviving more than five years after their diagnosis [19,20]. It has been observed that a good prognosis for women with OC is directly related to the severity of the disease at the time of diagnosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Findings included challenges related to diagnosis and treatment, adjustments in their relationships with family and/or friends, financial issues, some difficulties in their relationships with health professionals and comment on useful coping strategies. Through the use of template thematic analysis, these findings were further developed into a set of items that could be useful for the development of a values-based OC PROM (Additional file 1 ) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%